Seismic axial loads in steel moment resisting frames - Shen, Jay; Akbas, Bulent; Seker, Onur; Doran, Bilge; Wen, Rou; Uckan, Eren (KOREAN SOC STEEL CONSTRUCTION-KSSC, 2015)
During the 1994 Northridge Earthquake, many buildings with modern steel moment resisting frames (SMRFs) suffered from connection failures. One year later, similar damage has occurred in the 1995 Kobe earthquake in Japan. The unexpected seismic response of SMRFs resulted in comprehensive analytical and theoretical investigations and major changes in steel building design have been implemented consequently. One of the requirements in the subsequent seismic design codes is the stability check of the columns. Column yielding in a seismic force resisting systems (SFRSs) is not the desired damage mode and might result in column rupture or global buckling and threaten life safety. This study focuses on exploring the seismic axial loads for columns in SMRFs under strong ground motions. For this purpose, the increase in axial loads in low-, medium-, and high-rise SMRFs are investigated at the maximum lateral load level and the corresponding lateral displacement. The results are presented in terms of PHRs, average system overstrength factors (Omega(0)) of all columns in the frames under the selected ground motions, the distribution of Omega(0) in the individual columns in the frame, and axial load levels in columns. The results indicate that axial load level remains below 0.4 in the columns for low- and medium-rise frames, whereas it may get as high as 0.95 in highrise frames.
Keywords: special steel moment frames; amplification factor; system overstrength factor; nonlinear dynamic time history analyses; axial load level; PERFORMANCE; BEHAVIOR; Construction & Building Technology; Engineering